2013
DOI: 10.1530/eje-12-1101
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of everolimus in patients with metastatic insulinoma and refractory hypoglycemia

Abstract: Background: Refractory hypoglycemia in patients with metastatic insulinoma is an important cause of morbidity and mortality. Everolimus could be a new therapeutic option. Methods: Within the French Group, we conducted a retrospective, multicentric study of endocrine tumors to evaluate the time to the first recurrence of symptomatic hypoglycemia, after everolimus initiation, in patients with metastatic insulinoma and refractory hypoglycemia. Ongoing hyperglycemic medical options, tumor response, and safety info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 41 publications
0
64
0
4
Order By: Relevance
“…Interestingly, Kulke et al (72) first reported in 2009 that the use of everolimus in four patients with insulinoma and refractory hypoglycemia was associated with improved glycemic control. This 'beneficial' hyperglycemic effect of mTOR inhibitors in patients with metastatic insulinoma has since been confirmed in a large size study (73). This effect of mTOR inhibitors in cases of severe insulinoma is another proof of the hyperglycemic effect of this therapeutic class.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 74%
“…Interestingly, Kulke et al (72) first reported in 2009 that the use of everolimus in four patients with insulinoma and refractory hypoglycemia was associated with improved glycemic control. This 'beneficial' hyperglycemic effect of mTOR inhibitors in patients with metastatic insulinoma has since been confirmed in a large size study (73). This effect of mTOR inhibitors in cases of severe insulinoma is another proof of the hyperglycemic effect of this therapeutic class.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 74%
“…Conversely, patients with malignant unresectable insulinomas may take great advantage of this effect, as shown by some retrospective studies in this setting (Bernard et al 2013;Ferrer-Garcia et al 2013). Therefore, everolimus could be employed as first line treatment for progressive malignant insulinomas with refractory hypoglycaemia, as suggested by recent guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 8 retrospective studies were identified (Bernard et al 2013;Capdevila et al 2015;Ferrer-Garcia et al 2013;Fiebrich et al 2011;Kulke et al 2009;Liu et al 2016;Panzuto et al 2014;Tippeswamy et al 2015), which included a total of 183 patients with pancreatic and 135 patients with extra-pancreatic NETs (see Table 2a). …”
Section: Published Retrospective Studiesmentioning
confidence: 99%
“…Conservative treatment with use of diazoxide is not always effective, and the adverse effects are often observed [2]. Therefore, new methods of treatment are proposed with use of somatostatin analogues, mTOR inhibitor (everolimus), tyrosine kinase inhibitor (sunitinib), peptide receptor radionuclide therapy (PPRT), chemoembolisation, and radiofrequency or alcoholic ablation [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%